A case report of X-linked hypophosphatemia combined with primary hyperparathyroidism - Wu, YinQiong; Yang, Min; Zhang, Ying; Wang, Qin (Frontiers in Endocrinology, 2025)
Both hypophosphatemic osteomalacia and primary hyperparathyroidism (PHPT) can lead to hypophosphatemia, but their simultaneous occurrence in the same patient is exceedingly rare. This article reports a case of a 43-year-old female patient whose primary clinical manifestations included pain in the lumbosacral and scapular regions, restricted mobility, and biochemical findings of decreased serum phosphate levels with normal parathyroid hormone (PTH) levels. The patient’s symptoms improved after treatment with active vitamin D supplementation, although neutral phosphate supplements were not administered. Eight years later, the patient’s symptoms progressively worsened. Further investigations revealed elevated PTH levels and worsening hypophosphatemia. Neck contrast-enhanced ultrasonography and parathyroid radionuclide imaging both indicated nodules in the right parathyroid gland. Postoperative pathological examination confirmed the diagnosis of parathyroid adenoma. Whole-exome sequencing identified a heterozygous deletion in exon 11 of the PHEX gene, consistent with a diagnosis of X-linked hypophosphatemia (XLH).